Assistance in Improving Literacy and Halal Certification for MSMEs in Kalisalak Village - Larasati, Primadhani Dyah; Handayani, Bestari Dwi; Murtini, Henny; Gimnastiar, Mochammad Taufiq; Hutabarat , Widia Sari (Universitas Negeri Semarang, 2025)
Kalisalak Village is one of the villages in Batang Regency, the increase in the number of MSME actors in the village has not been accompanied by maximum efforts in improving the quality of MSME products themselves such as low business license management of both NIB, PIRT, HAKI and halal certification by MSME actors. The problems faced by MSME actors in Kalisalak Village result in a lack of competitiveness from existing MSME products, resulting in suboptimal sales. This community service aims to solve the problems experienced by partners, namely through education and socialization about business legality, halal certification on MSME products, and assistance in managing halal certification on products owned by MSMEs. This service helps the realization of the Sustainability Development Goals (SDGs), especially number 8, namely equitable village economic growth. The Focus Group Discussion (FGD) method was used to educate villagers on how to obtain business legality and halal certification, including the requirements. MSMEs gained a deeper understanding of the importance of halal products and business legality through MSME training and mentoring. Quantitatively, three MSMEs are planning to start the NIB management process, and one other person has shown serious interest in applying for halal certification.